Comprehensive investigating of mismatch repair genes (MMR) polymorphisms in participants with chronic hepatitis B virus infection - Ma, Ning; Sun, Yucheng; Kong, Yanan; Jin, Yiyao; Yu, Fengxue; Liu, Lianfeng; Yang, Lei; Liu, Wenxuan; Gao, Xia; Liu, Dianwu; Zhang, Xiaolin; Li, Lu (Frontiers in Genetics, 2023)
Background and aim: In this study, we focused on the relationship between single nucleotide polymorphisms in MMR genes and the occurrence and development of HBV infection. Materials and methods: A total of 3,128 participants were divided into five groups: negative control group (NeC), spontaneous clearance group (SC), chronic hepatitis B group (CHB), liver cirrhosis group (LC) and hepatocellular carcinoma group (HCC), CHB, liver cirrhosis and hepatocellular carcinoma constitute HLD. We conducted three case-control studies: NeC (840 cases) vs. HLD (1792 cases), SC (486 cases) vs. HLD (1792 cases) and CHB + LC (1,371 cases) vs. HCC (421 cases). 11 polymorphic loci in MLH1, MLH3, MSH5, PMS1 and PMS2 were involved in genotyping by Sequenom MassArray. The SNPStats performed Hardy-Weinberg equilibrium test. Linkage disequilibrium patterns were visualized using Haploview4.2. The GMDR (v0.9) was conducted to generalized multifactor dimension reduction analysis. The correlation, multiplicative interaction and additive interaction analyses were calculated by Logistic Regression through SPSS21.0. Matrix and programmed excel were also involved in the calculation of additive interaction. Results: In NeC vs. HLD group, MSH5-rs1150793(G) was a risk base to HBV susceptibility (nominal p = 0.002, OR = 1.346). We found multiplicative interaction between MLH1-rs1540354 (AA + AT) and PMS1-rs1233255 (AA) (nominal p = 0.024, OR = 1.240). There was additive interaction between PMS1-rs1233255 (AA) and PMS1-rs256554(CA + CC). In SC vs. HLD group, MLH1-rs1540354 (TT) was a risk genotype (nominal p < 0.05, OR>1). Through haplotype analysis, we found the linkage disequilibrium of three loci in MLH1. The results of GMDR showed the optimal five-locus model about the spontaneous clearance of HBV. In CHB + LC vs. HCC group, PMS2-rs12112229(A) was related to the cancerization of liver. Conclusion: We found rs1150793(G), rs1540354(T) and rs12112229(A) were significantly related to HBV susceptibility, spontaneous clearance of HBV and cancerization after infection, respectively.